Effect Of Slope Adjustment On Curve Number Using Global Digital Elevation Data: New Look Into Sharply-Williams And Huang Methods - Akbari, Abolghasem; Azizan, Abu Samah; Ngien, S. K. (2016)
The Natural Resources Conservation Service Curve Number (NRCS-CN) method is highly recommended for runoff prediction in many climate conditions. The key parameters to obtain CN values are hydrologic soil groups and land use information with respect to soil moisture conditions. This method has been well documented and available in many popular rainfall-runoff models such as HEC-HMS, Mike, SWAT and many more. It is also easy to implement due to availability of required data in many countries. However, it is criticized in a way that NRCS-CN do not take into account the effect of terrain slope and drainage area. This study aimed to investigate the effect of slope on CN and the way that slope could change the domain of CN values in Kuantan River Basin (KRB), Malaysia. The Huang and Sharply-Williams methods were used to investigate the changes on CN values provided in National Handbook of Engineering. The Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) Global Digital Elevation Model (GDEM) version 2 was used to derive slope map with spatial resolution of 30 m for the study area. The study significantly enhanced the application of GIS tools and recent advances in earth observation technology in order to analyze hydrological process with respect to spatial dimension.